People living with chronic pain in Canada face difficult decisions and decisional conflict concerning their care: data from the national DECIDE-PAIN survey - Florian Naye; France Légaré; Chloé Cachinho; Thomas Gérard; Karine Toupin-April; Maxime Sasseville; Jean-Sébastien Paquette; Annie LeBlanc; Isabelle Gaboury; Marie-Eve Poitras; Linda C. Li; Alison M. Hoens; et al. (BMC Primary Care)
Abstract Background Shared decision-making is an imperative in chronic pain care. However, we know little about the decision-making process, especially in primary care where most chronic pain care is provided. We sought to understand decisional needs of people living with chronic pain in Canada. Methods We conducted a population-based cross-sectional online survey of random samples of adults living in Canada with chronic noncancer pain and registered with the Leger Marketing panel. We followed the International Association for Study of Pain definition of chronic pain (i.e., persistent or recurrent pain lasting longer than three months). We used a stratified proportional random sampling based on the population and chronic pain prevalence of each province to achieve representativeness. Based on the Ottawa Decision Support Framework, we collected data on difficult decisions (i.e., decision with more than one option and no clear best option) related to their chronic pain condition, the level of decisional conflict associated with the most difficult decisions (i.e., Decisional Conflict Scale), the assumed and preferred role during the decision-making process (i.e., Control Preferences Scale), and respondents’ characteristics. We used descriptive quantitative analyses of survey responses. Results Of the 31,545 invited panellists, 2,666 met the eligibility criteria, and 1,649 respondents from the 10 Canadian provinces completed the survey. Respondents had diverse socio-demographic profiles. Mean age was 51.8 years (SD = 16.3). Half were men (51.4%), most lived in urban areas (87.8%), mean pain duration was 8.5 years (SD = 9.6), and respondents reported an average number of painful body regions of 2.3 (SD = 1.5). We observed that 96.7% of respondents faced at least one difficult decision across their care pathways. These difficult decisions were related to numerous issues from the medical consultation, diagnosis, treatment, and daily life. Almost half of respondents made their most difficult decision with a primary care physician. One third of respondents experienced a high level of clinically significant decisional conflict (Decisional Conflict Scale score ≥ 37.5). Two-thirds of respondents self-reported having a collaborative role during their decision while three-quarters wanted this role. Conclusions People living with chronic pain in Canada have unmet decisional needs and need support to make optimal decisions to manage their chronic pain. Our findings will guide future development of interventions to implement shared decision-making, especially to support primary care where discussions about difficult decisions often occur.